(untitled) (Bangladesh Journal of Pharmacology, 2015)
Jatropha gossypifolia is used in folkloric system to manage emesis and gastrointestinal motility disorders such as constipation and diarrhea. The present study was undertaken to provide pharmacological evidences for these folkloric uses by in vivo and in vitro experimental setting. Ethanolic extract of J. gossypifolia showed the significant antiemetic potential (p<0.05) against different emetogenic stimuli, when compared with chlorpromazine. The extract (0.01-1.0 mg/mL) on application to isolated rabbit jejunum preparation exerted spasmogenic effect, followed by the spasmolytic effect (3-10 mg/mL). In the presence of atropine, spasmogenic effect was blocked while spasmolytic effect was emerged, suggesting the involvement of muscarinic receptor activation. J. gossypifolia caused relaxation of high K+ (80 mM)-induced contraction and shifted the Ca2+ concentration-response curve to the right in a manner similar to verapamil, thus conforming its Ca2+-channel blocking activity. These findings provide pharmacological validation for the presence of antiemetic and gut modulator (spasmogenic and spasmolytic) activates, validating its folkloric uses.